2022
DOI: 10.1093/cei/uxac103
|View full text |Cite
|
Sign up to set email alerts
|

A close-up on the expanding landscape of CD21–/low B cells in humans

Abstract: Memory B cells (MBCs) are an essential part of our immunological memory. They respond fast upon re-encountering pathogens and can differentiate into plasma cells that secrete protective antibodies. The focus of this review is on MBCs that lack, or express low levels of, CD21, hereafter referred to as CD21-/low. These cells are expanded in peripheral blood with age and during chronic inflammatory conditions such as viral infections, malaria, common variable immunodeficiency, and autoimmune diseases. CD21-/low M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…We then carried out detailed profiling of PBMCs using two different well-established gating/classification strategies that allow to distinguish B cell populations based on IgD and CD27 and CD24 and CD38 expression [ 16 , 27 ]. This strategy enabled us to identify the following populations within the CD19 + B cell compartment: IgD + CD27 - naïve, IgD - CD27 + class-switched and IgD + CD27 + unswitched memory, IgD - CD27 - DN cells, CD24 hi CD38 hi transitional, CD24 int CD38 int mature, CD24 hi CD38 lo total memory, CD24 lo CD38 lo activated B cells, and CD24 int CD38 hi pre-plasmablasts.…”
Section: Resultsmentioning
confidence: 99%
“…We then carried out detailed profiling of PBMCs using two different well-established gating/classification strategies that allow to distinguish B cell populations based on IgD and CD27 and CD24 and CD38 expression [ 16 , 27 ]. This strategy enabled us to identify the following populations within the CD19 + B cell compartment: IgD + CD27 - naïve, IgD - CD27 + class-switched and IgD + CD27 + unswitched memory, IgD - CD27 - DN cells, CD24 hi CD38 hi transitional, CD24 int CD38 int mature, CD24 hi CD38 lo total memory, CD24 lo CD38 lo activated B cells, and CD24 int CD38 hi pre-plasmablasts.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the relatively few studies regarding B cell subsets in patients with eRA, our current report is unique as it separates the B cell populations according to expression levels of the complement 2 receptor, CD21. Lack of or low levels of CD21 on B cells are characteristic of pathologies related to some chronic infections and autoimmunity [ 22 ]. We have both identified changes in the composition of the B cell population and additionally analysed those in relation to clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have in addition to the DN subset also shown SWM to be a significant component of the SF B cell compartment [ 35 , 36 ]. CD21 −/low B cell subset in different chronic autoimmune and inflammatory conditions have been described using diverse markers, but a common characteristic of these subsets is the expression of CD11c and Tbet [ 22 ]. Indeed, our CD21 −/low DN SF subset is mainly CD11c + Tbet + .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the therapy with natalizumab, an antibody to α4 integrins, leads to a preferential expansion of the memory B-cell pool, which is attributable to a decreased retention of these cells within secondary lymphoid tissues [ 66 68 ]. At the same time, the proportion of CD21 −/low CD38 −/low B cells, which have been shown to be enriched with autoreactive unresponsive clones in some autoimmune diseases [ 47 , 69 ], was significantly lower in patients on IRTs but significantly higher in patients on natalizumab therapy. Further research on CNS-resident and antigen-specific B cells may provide deeper insights into the therapeutic mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%